ЕКОЛОГІЗАЦІЯ ЗАХОДІВ РЕГУЛЮВАННЯ ЧИСЕЛЬНОСТІ ФІТОФАГІВ ЯК ШЛЯХ ДО ЗБЕРЕЖЕННЯ І ВІДТВОРЕННЯ ЕНТОМОЛОГІЧНОГО АГРОБІОРІЗНОМАНІТТЯ - Лісовий , М.М.; Пархоменко , О.Л.; Пархоменко , Т.Ю.; Чайка , В.М. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2010)
The wide introduction of biological methods of pests control on main vegetables and potato promotes obtaining of environmentally safe products for baby and dietic nourishment as well as preservation of entomological agrobiodiversity. Selected new strain B. thuringiensis 0376 have shown the high biological population control efficiency not only against Phtorimea operculella Zel. during the vegetation and the storage of potato yield but also against Brevicoryne brassicae L. on the cabbage fields. At single application the additional stored cabbage yield made out 59 c/ha (90% to control).